2014
DOI: 10.1111/tbj.12335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Steroid Treatment on Idiopathic Granulomatous Mastitis: Clinical and Radiologic Evaluation

Abstract: Idiopathic granulomatous mastitis (IGM) is a rare inflammatory, noncaseating, chronic granulomatous benign disease. The etiology of IGM is still unknown. It is postulated to be an autoimmune localized response. The use of a course of oral steroids provides an important regression of breast mass and skin lesions. Topical corticosteroids are used to treat many skin diseases, but no study is available on the sole use of topical steroids for treating IGM. Eleven women with IGM were treated with topical steroid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…The characteristic of reviewed articles is summarized in Table (). The total number of articles was 70, 59 in group A and 11 in group B.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic of reviewed articles is summarized in Table (). The total number of articles was 70, 59 in group A and 11 in group B.…”
Section: Resultsmentioning
confidence: 99%
“…In the patient shown in figure 1, the authors observed a 50% reduction of the breast mass after 3 weeks of therapy with topical hydrocortisone acetate. No side effects occurred [35]. …”
Section: Resultsmentioning
confidence: 99%
“…One reported case successfully treated by using a treatment combination of low‐dose oral + topical steroid applications . The first study with local steroids, conducted as a topical application on the skin only, was performed by Gündüz et al In their study, steroid treatment was performed as a topical application to the skin for 12 weeks in 11 patients with IGM. According to the study were as effective in parenchyma as they were in cutaneous lesions.…”
mentioning
confidence: 99%